Rigid Amorphous Phase: Mechanical and Transport Properties of Nitrile Rubber/Clay Nanocomposites. Issue 2 (May 2017) - Thomas, Saliney; George, Soney C.; Thomas, Sabu
The present study has been focused on the preparation of nitrile rubber/ organoclay nanocomposites containing 0–10 wt% Cloisite 93A by mechanical mixing on a two-roll mill. The rubber samples were vulcanized by accelerated sulfur vulcanization process. The role of nanoclay on the curing process has been carefully studied. The clay dispersion in the rubber matrix was analyzed by high resolution transmission electron microscopy (TEM) and X-ray diffraction studies. Both XRD and electron microscopic analyses indicated that the nanocomposites exhibit partly intercalated and exfoliated structure. However, the nanocomposites showed better exfoliation at lower clay loading (2 wt percent) as evident by TEM and XRD. At higher clay loading the clay tend to form aggregates. The correlation distance and the length and thickness of the clay platelets in the rubbery matrix have been deduced from the TEM micrographs as a function of clay loading. The nanoclay-rubber interaction has been quantified by Kraus analysis. The nanocomposites exhibited improved mechanical properties which include tensile strength, modulus, tear strength and resistance to abrasion. The solvent resistance of the nanocomposite increased with the increase in dosage of the nanofiller. Finally, the properties have been modeled using Guth and Halpin-Tsai equations.